Learning from the transfer of a fellowship programme to support primary care workforce needs in the UK: a qualitative study. Issue 1 (25th January 2019) - Bryce, Carol; Russell, Rachel; Dale, Jeremy
Abstract : Objectives: Service redesign, including workforce development, is being championed by UK health service policy. It is allowing new opportunities to enhance the roles of staff and encourage multiprofessional portfolio working. New models of working are emerging, but there has been little research into how innovative programmes are transferred to and taken up by different areas. This study investigates the transferability of a 1-year post-Certification of Completion of Training fellowship in urgent and acute care from a pilot in the West Midlands region of England to London and the South East. Design: A qualitative study using semistructured interviews supplemented by observational data of fellows' clinical and academic activities. Data were analysed using a thematic framework approach. Setting and participants: Two cohorts of fellows (15 in total) along with key stakeholders, mentors, tutors and host organisations in London and the South East (LaSE). Fellows had placements in primary and secondary care settings (general practice, emergency department, ambulatory care, urgent care and rapid response teams), together with academic training. Results: Seventy-six interviews were completed with 50 participants, with observations in eight clinical placements and two academic sessions. The overall structure of the West Midlands programme was retained and the core learning outcomes adopted in LaSE. Three fundamental adaptations were evident: broadening the programme to include multiprofessional fellows, changes to the funding model and the impact that had on clinical placements. These were felt to be key to its adoption and longer-term sustainability. Conclusion: The evaluation demonstrates a model of training that is adaptable and transferable between National Health Service regions, taking account of changing national and regional circumstances, and has the potential to be rolled out widely.